TEKNIK PELARASAN GAMELAN JAWA PADA INSTRUMEN GENDER DAN GONG - Risnandar Risnandar (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2017)
AbstractThis study about the tuning of the gender and gong in Javanese gamelan is an attempt to formulate a technique for Javanese gamelan tuning. There are a number of problems concerning gamelan tuning that in the past have always been a mystery. There has never been any systematic written documentation about the theory or method of gamelan tuning. Traditionally, the process of knowledge transfer takes place in the family environment of the gamelan tuner during the tuning process in the workshop (besalen). This makes it difficult for the next generation of tuners to imitate their seniors. Therefore, it is possible that someday the technique or knowledge of tuning will become distorted or even disappear along with the death of the old generation of gamelan tuners. The goal of this research is to formulate a technique and seek answers to various questions about the tuning of the gender and kempul from the perspective of the gamelan tuner. The focus of this study is to uncover problems related to the technique and process of tuning the gender and gong. Hence, the research uses a qualitative method, collecting and processing as much data as possible from gamelan tuners, gamelan owners, and artists. In this way, it is hoped to discover the various problems surrounding the tuning of the gender and gong in Javanese gamelan. Keywords: technique, tuning, gender, gong. AbstrakPenelitian tentang pelarasan gender dan gong gamelan Jawa ini merupakan usaha untuk merumuskan teknik pelarasan gamelan Jawa. Terdapat berbagai persoalan yang selama ini masih menjadi misteri dalam pelarasan gamelan. Belum terdapat teori ataupun cara kerja pelarasan gamelan yang tertulis secara sistematis. Proses transfer knowlage terjadi secara tradisional di lingkungan keluarga pelaras saat proses pengerjaan di besalen. Hal ini mengakibatkan generasi penerus sulit untuk menirukan generasi seniornya. Dengan demikian dimungkinkan suatu saat teknik ataupun ilmu pelarasan akan mengalami distorsi atau bahkan hilang seiring dengan meninggalnya umpu pelaras gamelan. Penelitian ini bertujuan untuk merumuskan teknik dan juga mencari jawaban berbagai persoalan pelarasan gender dan kempul dilihat dari sudut pandang pelaku (pelaras gamelan). Fokus dari penelitian ini adalah mengungkap persoalan-persoalan terkait dengan teknik dan proses pelarasan gender dan gong. Bertolak dari sudut pandang ini maka penelitian akan menggunakan metode kualalitatif dengan mengumpulkan dan mengolah data sebanyaknya dari pelaras (pelaku), pemilik gamelan, dan seniman sebagai pemakai. Melalui cara ini diharapkan mampu mengungkap berbagai persoalan pelarasan gender dan gong gamelan Jawa. Kata Kunci: teknik, pelarasan, gender, gong.